Poor School Academic Performance and Benign Epilepsy with Centro-Temporal Spikes - Vetri, Luigi; Pepi, Annamaria; Alesi, Marianna; Maltese, Agata; Scifo, Lidia; Roccella, Michele; Quatrosi, Giuseppe; Elia, Maurizio (Behavioral sciences, 2023)
Background: Poor academic performance of students with epilepsy seems to be a multifactorial problem related to difficulties in reading, writing, math, and logic skills. Poor school and academic performances refer to learning problems in a specific academic area due to learning disorders and learning difficulties not excluding the ability to learn in a different manner during school and academic life. Sometimes, school, academic difficulties, and Rolandic epilepsy can coexist together, and there may be comorbidities. Consequently, the risk of impaired academic performance in people with epilepsy is high. Methods: This review analyzed the relationship between Benign Epilepsy with Centro-Temporal Spikes (BECTS) and poor school and academic performance (PSAP) in children and adolescents (aged 6 to 19), and in adults (aged 20 to no age limit). The PRISMA guideline was used to guide our review strategy. Results: This research shows that Benign Epilepsy with Centro-Temporal Spikes (BECTS) and poor school and academic performances are strongly correlated. An early onset age, as well as a long persistence of seizures, correlate more closely with PSAP. On the other hand, it appears that good pharmacological control of seizures and remission from the acute phase of the pathology support better school performance. Conclusions: This review highlights how neuropsychological aspects are also involved in patients with BECTS and PSAP, both in the greater predisposition to the establishment of other neuropsychiatric conditions and in the possibility that stigma conditions and poor academic results may have repercussions on the adaptation and functioning of these subjects. Global management of the subject with BECTS and PSAP is essential, which also pays attention to the aspects of social and scholastic inclusion, both to achieve age-appropriate educational and behavioral objectives, to give the necessary tools for the growth of the individual, and to allow a serene transition to adulthood, favoring autonomous learning and better outcomes.